Evaluation of the Effectiveness and Adaptability of a Composite Water Control Process for Horizontal Wells in Deepwater Gas Reservoirs - Wang, Dianju; Li, Yihe; Ma, Lan; Yu, Fahao; Liu, Shufen; Qi, Tong; Jiang, Siyuan (Frontiers in Earth Science, 2022)
Deepwater gas fields have high bottom water energy and high risk of seeing water. Higher requirements are put forward for the water control process to control the water effect. This paper is based on the actual background and well design of the X gas field in the South China Sea, based on three sets of physical simulation experiments and three sets of numerical simulation experiments. The analysis and comparison of the water control effect of the combination of continuous packer, continuous packer and variable density screen tube and their adaptability evaluation in deepwater gas reservoirs are completed. The results obtained from the numerical and physical simulations are consistent. The experimental results show that the water control process of continuous packer is mainly based on the water seeing and water blocking. It is less capable of extending the time to water in the horizontal section. However, its water blocking ability is strong and it is able to seal the water spot quickly. It extends the total production time by 12.29% and increases the total gas production by 5.96%; the combined water control process of continuous packer and variable density screen tube can effectively play their respective advantages of water control. The combination of continuous packer and variable density screen tube can effectively play the advantages of their respective water control processes, enabling the gas-water interface to advance in a balanced manner, extending the water-free gas recovery period by 11.61%, extending the total gas production time by 15.76% and increasing the total gas production volume by 13.75%. Both water control processes have good applicability in deepwater gas fields. and have certain sand control capability. It is conducive to the one-time completion operation for the commissioning of deepwater gas fields.